The Effect of Compliance in Using Doctor Apps, Time Management, and Teamwork on Operation Timeliness in Tangerang Private Hospitals - Prieely, Chyntia; Indrawati, Ratna; Andry, Andry (YCMM, 2025)
The timeliness of operations in hospitals is essential for service efficiency, but is often constrained by factors such as compliance with the use of doctor applications. This study analyzes the effect of compliance in the use of Doctor Apps, time management, and teamwork on operation timeliness in private hospitals in Tangerang Regency. The aim is to test compliance in using doctor apps, time management, and teamwork on surgery timeliness in hospitals. This study used a quantitative approach with multiple linear regression analysis on questionnaire data from 96 doctors and health workers. Hypothesis testing used the t-test, F-test (ANOVA), and coefficient of determination analysis (R²), at a significance level of 0.05. The results of the regression analysis showed that only X2 (Time Management) had a significant effect on operation timeliness (significance 0.000), while X1 (Compliance Doctor Apps) and X3 (Teamwork) were not significant (significance> 0.05). Regression analysis showed that X2 (Time Management) affected the punctuality of surgery (significance 0.000, X1 (Compliance Doctor Apps) and X3 (Teamwork) were not significant (significance >0.05). This regression model was statistically significant (F=7.480; p=0.000), with a correlation value (R) of 0.443. In conclusion, compliance in the use of doctor applications, time management, and teamwork significantly affected the punctuality of surgery in private hospitals in Tangerang, although their contribution was relatively limited. Optimization of doctor applications, time management, and teamwork is recommended for operational efficiency.